Review of the experience gained so far in enforcement cooperation, including at the regional level (UN New YorkUS, 2011)
Examines the experiences gained in competition law enforcement cooperation, highlighting aproaches taken to deepen cooperation in enforcement practice and share information and best practices.
Keywords: COMPETITION LAW